Active subsurface structures at Fayoum- Cairo district, Northern Western Desert, Egypt, as deduced from magnetic data - BRIMICH, Ladislav; KHALIL, Ahmed; KORDÍK, Pavel; MEKKAWI, Mahmoud; EL-BOHOTY, Mohamed; REFAI, Mohamed Khalil; KADER, Abdou Khalaf Abdel (Contributions to Geophysics and Geodesy, 2011)
In the present work, we present a reconnaissance study to elucidate and delineate the subsurface structures and tectonics of the area between Dahshour and El Fayoum province using available magnetic data; including land magnetic survey and aeromagnetic data. The study area has been selected due to its active tectonic situation. The magnetic data have been analyzed to provide new information about the tectonic setting and subsurface structures of the study area. A detailed land magnetic survey has been carried out for the total component of geomagnetic field using two Proton magnetometers, one of them as a local reading base station placed in the middle part of the area, while the second was used for measuring the total intensity of the different points in a mesh-like configuration. The necessary corrections for the measured magnetic data have been carried out. The total land intensity and aeromagnetic maps have been reduced to the north magnetic pole. Moreover, wave number filtering technique has been carried out on the magnetic data utilizing three types of filters with varying wavelengths. The application of these tools on magnetic data discriminated the variable sources of specific depth ranges for the residual and regional anomalies, as well as those limited to a certain depth interval. It was found that the main tectonic trends taken the directions NE–SW, NW–SE and E–W. Three basement cross-sections have been generated using the 2-D modeling to support the interpreted structures and give idea about the configuration of subsurface basement shape. Depth estimations have been conducted by application of the Power spectrum, analytical signal and 2-D modeling techniques. The results indicate that the average calculated depth ranges between 1.8 km to 3.5 km, while the depth to volcanic intrusions ranges between 0.20 km and 0.30 km.